DIGITAL JOURNALING FOR STRESS MANAGEMENT IN INTERNATIONAL STUDENTS - Shereen Mohamed; Cahyaning Suryaningrum; Yuni Nurhamida (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
International students experience different stressors in host countries, stressors related to acculturation, academic pressure, and social integration. Adversely affecting their mental health. Studies addressed the significance of coping strategies as a tool for managing stress and relieving distress feelings. This study aimed to evaluate the efficacy of a digital journaling intervention in reducing perceived stress among this population. Based on Pennebaker’s expressive writing theory, the program employed a one-week intervention using the "Unstuck" CBT-based journaling app with four first-semester international students in Indonesia. A mixed methods approach was used, with pre- and post-test measurements via the Perceived Stress Scale (PSS) and qualitative feedback discussions. Statistical analysis using the Wilcoxon Signed-Rank Test showed no significant difference in stress scores post-intervention (p=0.357), likely due to the extremely small sample size limiting statistical power. However, a descriptive trend indicated reduced stress for three of the four participants. Qualitatively, participants reported increased self-awareness and emotional clarity, highlighting journaling's role in facilitating emotional disclosure and self-discovery. The study concludes that while digital journaling shows promise as a low-cost, accessible tool for promoting self-reflection, its measurable impact on stress reduction requires further investigation with a larger sample, longer intervention duration, and a controlled research design.